Partial credit guarantees and SMEs financing - Boschi, Melisso; Girardi, Alessandro; Ventura, Marco (Journal of Financial Stability, 2014)
Using data for the Italian Central Guarantee Fund for Small and Medium Enterprises, the paper analyses the effect of partial credit guarantees on firms’ financing. We show that neglecting heterogeneity in guarantee intensities, namely considering all firms as equally treated, leads to a mis-measurement of the additionality effect. Moreover, we document the existence of non-linear effects, suggesting that coverage ratios below a certain threshold are likely to be ineffective to lessen obstacles faced by firms when seeking external financing funds.